2014
DOI: 10.1016/j.apcatb.2013.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Proposed transformation pathway and evolution profile of diclofenac and ibuprofen transformation products during (sono)photocatalysis

Abstract: Liquid chromatography time-of-flight mass spectrometry (UPLC/ESI-QToF-MS) was used for the elucidation of the main transformation products (TPs) resulting from the degradation of diclofenac (DCF) and ibuprofen (IBP) during the application of various advanced oxidation processes in aqueous matrices. The examined processes were TiO 2 photocatalysis driven by UV-A or simulated solar irradiation, sonolysis, and UV-A photocatalysis integrated with ultrasound irradiation (sonophotocatalysis). A comparison between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(55 citation statements)
references
References 67 publications
5
46
0
4
Order By: Relevance
“…Several studies have investigated DCF removal in the advanced oxidation processes. Michael observed an 80% DCF (the initial concentration was 10 mg L −1 ) removal efficiency in 120 min with TiO 2 as the catalyst under a sonocatalytic process [45]. Shan found that 80% DCF (the initial concentration was 20 mg L −1 ) was removed in 40 min with FeCeO x under an ultrasonic system [46].…”
Section: Photocatalytic Activity Of the Ag 3 Po 4 /G-c 3 N 4 Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated DCF removal in the advanced oxidation processes. Michael observed an 80% DCF (the initial concentration was 10 mg L −1 ) removal efficiency in 120 min with TiO 2 as the catalyst under a sonocatalytic process [45]. Shan found that 80% DCF (the initial concentration was 20 mg L −1 ) was removed in 40 min with FeCeO x under an ultrasonic system [46].…”
Section: Photocatalytic Activity Of the Ag 3 Po 4 /G-c 3 N 4 Compositesmentioning
confidence: 99%
“…Several studies have investigated DCF removal in the advanced oxidation processes. Michael observed an 80% DCF (the initial concentration was 10 mg L −1 ) removal efficiency in 120 min with TiO2 as the catalyst under a sonocatalytic process [45]. …”
Section: Photocatalytic Activity Of the Ag3po4/g-c3n4 Compositesmentioning
confidence: 99%
“…Similar pattern was also applied during the sonophotocatalytic degradation of diclofenac. Similarly, the degradation pattern of ibuprofen involved hydroxylation, demethylation, decarboxylation, cleavage of isobutyl moiety and oxidation of hydroxyl groups (Michael et al 2014). Twenty intermediate products are reported during the sonophotocatalytic degradation of ofloxacin.…”
Section: Sonoelectrochemical Methodsmentioning
confidence: 99%
“…The degradation rate of ibuprofen is 49 9 10 -3 min -1 and that of diclofenac is 40 9 10 -3 min -1 with conversion percentage of 85 % for ibuprofen and 96 % for diclofenac, respectively Michael et al (2014) Environ Chem Lett …”
Section: Tiomentioning
confidence: 99%
“…Concerning these compounds, there are several works reporting AOPs to treat diclofenac (Calza et al, 2006;Guyer and Ince, 2011;Martínez et al, 2011;Michael et al, 2014;Naddeo et al, 2010;Naddeo et al, 2009;Pérez-Estrada et al, 2005;Rizzo et al, 2009;Zhang et al, 2011) as well as both hormones (Dimitroula et al, 2012;Frontistis et al, 2012;Frontistis et al, 2011;Pereira et al, 2012). Data regarding these particular compounds can be consulted in article reviews that have been published in the last few years and that already encompass a lot of information dealing with the removal of these compounds from water by using AOPs Kanakaraju et al, 2014;Klavarioti et al, 2009;Liu et al, 2009;Luo et al, 2014;Rivera-Utrilla et al, 2013;Silva et al, 2012).…”
Section: Pharmaceuticals Proposed For the First Watch List: Diclofenamentioning
confidence: 99%